قضايا ترجمة القرآن الكريم في ضوء دراسات الترجمة الحديثة - Abd. Rahman, Akmal Khuzairy (IIUM Press, 2019)
The book attempts to give insights into the aspects of translating the Quran from the modern perspectives of translation study